Strategies of the Head of Madrasah Tsanawiyah Abadiyah in Building a School of Excellence at National and International Levels - Sinta Ema Cholilah; Ambarwati Ambarwati (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe the leadership strategies employed by the principal of Madrasah Tsanawiyah Abadiyah to establish the school as an institution of excellence and achievement. The study employs a qualitative research design with a descriptive approach. The research focuses on the implementation of bottom-up strategies, transformative leadership, and motivational strategies in managing school programs. Data collection involved interviews, observations, and document analysis. A descriptive-qualitative analysis was conducted to provide an in-depth description of the principal's leadership practices in developing the institution's potential. The results indicate that the principal implements a bottom-up strategy by actively involving the entire school community in program planning and development, thereby fostering a sense of ownership and ensuring program relevance to students' needs. Transformative leadership is demonstrated through the ability to establish a vision of excellence and cultivate a culture of innovation and achievement. Furthermore, motivational strategies are applied by providing encouragement, appreciation, and guidance to students in both academic and non-academic activities, including competitions and extracurricular pursuits. The synergy of these three strategies contributes to enhancing the quality and achievements of Madrasah Tsanawiyah Abadiyah at both national and international levels. Thus, it can be concluded that the principal's leadership strategies play a crucial role in building a school that is excellent, competitive, and grounded in strong character.